Theodor W. Adorno and Arnold Gehlen: Political Contradictions and Cultural Critical Agreement - Rehberg, Karl-Siegbert (Scenari, 2021)
The relationship between Theodor W. Adorno and Arnold Gehlen, two politically and scientifically conflicting philosophers and sociologists who share some of the cultural-critical positions, is described. Both faced the cultural and political developments in the modern age with a skeptical view, fed from different sources, whereby the thinking of both was shaped by (very different) social catastrophes - the bitter experiences of exile on Adornos and the decline of the (class) Bourgeoisie on Gehlen's side. Four public discussions between the two opponents on radio and television are also outlined. Gehlen attributed the loss of social order he observed to a chain of political disasters, while Adorno emphasized the fate of capturing society through the principles of “reification” under the “exchange principle”. So one sees the proximity of a thinking out of negation, captured dialectically by Adorno and saturated with facts by Gehlen. Despite all the differences between these two scholars, it was the arts that brought the interlocutors into a closer relationship. The essay, which depicts the opposing and coinciding motifs of the two protagonists, is concluded with Hans Magnus Enzensberger's ode "difficult work" from 1965, singing Adorno's Negative Dialectic.